CEO Tenure and Entrepreneurial Orientation Within Family and Nonfamily Firms. (9th February 2015) - Boling, J. Ruben; Pieper, Torsten M.; Covin, Jeffrey G.
Abstract : The current research investigates how entrepreneurial orientation changes during a chief executive officer (CEO)'s tenure in family and nonfamily firms. Based on secondary data collected from 210 firms representing five industries, the results show an inverse U‐shaped relationship between CEO tenure and entrepreneurial orientation, consistent with the executive life cycle literature. Moreover, in family firms the shape of the inverse U is less pronounced and the level of entrepreneurial orientation peaks considerably later in the CEO's tenure when compared with nonfamily firms.